2007
DOI: 10.1080/14017430701383748
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of ventricular fibrillation requires central β-adrenoceptor blockade in rabbits

Abstract: Metoprolol reduced the incidence of VF by a better maintained discharge than atenolol in efferent cardiac vagal nerves, possibly due to inhibition of central nervous beta(1) adrenoceptors modulating vagal nervous outflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Dogs treated with metoprolol showed an increase in LV EF and a reversal of LV global, structural and biochemical remodelling (Imai et al ., 2007). Ablad et al . (2007) found metoprolol reduced the inducibility of ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs treated with metoprolol showed an increase in LV EF and a reversal of LV global, structural and biochemical remodelling (Imai et al ., 2007). Ablad et al . (2007) found metoprolol reduced the inducibility of ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs treated with metoprolol showed an increase in LV EF and a reversal of LV global, structural and biochemical remodelling (Imai et al, 2007). Ablad et al (2007) found metoprolol reduced the inducibility of ventricular fibrillation. In addition, remodelling of noninfarcted myocardium is associated with myofilament function, which may contribute to depressed LV function (van der Velden et al, 2004).…”
Section: Figurementioning
confidence: 99%
“…Previous studies also reported that metoprolol increased left ventricular ejection fraction (LVEF) and a reversal of left ventricular global, structural and biochemical remodeling in dogs [11]. Moreover, Ablad et al [12] found that metoprolol reduced the inducibility of ventricular fibrillation. Nevertheless, the potential role of metoprolol in chronic OSA-induced left ventricular structural remodeling remains unclear.…”
Section: Introductionmentioning
confidence: 90%
“…Sanderson et al 19 demonstrated superior effects of metoprolol over hydrophilic vasodilating β-blocker celiprolol in restoring baroreflex gain and vagal tone in patients with chronic HF. Similarly, recent evidence by Ablad et al (2007) obtained in anaesthetized rabbits suggested that β-blockers are acting centrally to increase cardiac vagal tone. In contrast, there are data obtained in normal human subjects 20,21 and in post-MI patients 22,23 indicating that the effects of β-blockers on vagal tone are likely to be due to their peripheral actions.…”
Section: Heart Failure Autonomic Control Of the Heart And Metoprololmentioning
confidence: 99%